Maximal buttonings of non-tree graphs - Wanchai Tapanyo (2018)
© 2017 by the Mathematical Association of Thailand. All rights reserved. Let G be a finite connected graph of n vertices v1, v2,…, vn. A buttoning of G is a closed walk consisting of n shortest paths [v1, v2], [v2, v3],…, [vn−1, vn], [vn, v1]. The buttoning is said to be maximal if it has a maximum length when compared with all other buttonings of G. The goal of this work is to find a length of a maximal buttoning of non-tree graphs: complete multipartite graphs, grid graphs and rooted products of graphs.